2001
DOI: 10.4049/jimmunol.166.12.7158
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to Cyclosporin A-Induced Autologous Graft-Versus-Host Disease Is Mediated by a CD4+CD25+ Subset of Recent Thymic Emigrants

Abstract: Our previous studies revealed that both the autoeffector and immunoregulatory T cells in cyclosporin A (CSA)-induced autologous graft-vs-host disease are recent thymic emigrants (RTEs). The autoeffector cells appear in and are released from the thymus during the first week of CSA treatment, whereas the immunoregulatory thymocytes appear during the second week but are not released until several days after cessation of CSA treatment. In the present study, the antigenic phenotypes of these functional T cell subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 40 publications
3
22
0
Order By: Relevance
“…In agreement with our findings, CsA treatment of newborn mice was found to cause autoimmune diseases similar to those observed following neonatal thymectomy, which also has a detrimental effect on T REG homeostasis. 38 Moreover, our data fit with the observations that CsA decreases the expansion of adoptively transferred FoxP3 þ T cells, 39,40 whereas rapamycin treatment spares T REG in vivo. 39,41 Decreased FoxP3 levels have been associated with GVHD in several studies.…”
Section: Discussionsupporting
confidence: 77%
“…In agreement with our findings, CsA treatment of newborn mice was found to cause autoimmune diseases similar to those observed following neonatal thymectomy, which also has a detrimental effect on T REG homeostasis. 38 Moreover, our data fit with the observations that CsA decreases the expansion of adoptively transferred FoxP3 þ T cells, 39,40 whereas rapamycin treatment spares T REG in vivo. 39,41 Decreased FoxP3 levels have been associated with GVHD in several studies.…”
Section: Discussionsupporting
confidence: 77%
“…Recent evidence from an animal model has demonstrated the presence of peripheral autocytotoxic T cells in the first 7 days following CsA treatment and persisting for up to 2 weeks following the cessation of CsA therapy. 32 However, autoregulatory T cells only appear peripherally after cessation of CsA therapy, suggesting that early upregulation of Class II expression using IFN may be more beneficial. Recent studies have suggested a role for nonmyeloablative SCT for patients relapsing post first autologous transplant; 33 however, few patients will have an eligible donor and an antilymphoma effect has not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, CsA is necessary for the development of autoGVHD, as animals receiving ASCT alone almost never develop pathological clinical symptoms. Recent studies have brought new insights into the mechanisms of action of CsA following ASCT by demonstrating that CsA is able to delay the emigration of CD4+ 25+ T-regulatory cells without affecting the departure of other T-cell subsets (8). It is thus tempting to speculate that, when CsA treatment is stopped, mature CD8+ and CD4+ 25-T cells can be activated and become effector cells leading to autoGVHD, the more so because T-regulatory cells still reside in the thymus.…”
Section: Discussionmentioning
confidence: 99%
“…Second, CsA is able to interfere with the thymic differentiation of T-cell subsets and may alter the kinetics of recovery of effector vs. regulatory cells. In this respect, Wu and Goldschneider have shown that thymus emigration of CD4+ 25+ regulatory T cells in CsA-treated mice occurs several days after the emigration of mature naïve autoreactive T cells (8). This delay in CD4CD25 T-cell recovery may lead to a transient lack of down-regulatory mechanisms, allowing activation of effector T cells and development of autoGVHD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation